Director Experience and the Performance of IPOs: Evidence from Sweden - Anna Thorsell; Anders Isaksson (Australasian Accounting, Business and Finance Journal, 2014)
An initial public offering (IPO) represents one of the final stages in the life of a small firm as it transitions from private to public. In this paper the experience of directors is examined to determine the extent of the role they play in ensuring a successful listing. Unique data from 122 IPOs on the Swedish Stock Exchange have been examined in a search for the effect of director experience on aftermarket performance. Specific aspects of director experience within a board, such as interlocking directorships and average tenure, are connected to the underpricing of Swedish IPOs. Contrary to expectations, no statistically significant relationship was found between long-run aftermarket performance and director experience at the time of an IPO. This suggests that the previous experience of directors, as measured in earlier studies, is less relevant to long-term aftermarket performance in Sweden compared to other countries studied in the literature review. This emphasises the importance of examining different institutional contexts.
Keywords: Initial Public Offerings; The Board of Directors; Corporate Governance; Underpricing; Aftermarket Performance